2014
DOI: 10.1007/s10646-014-1299-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cd, Co, Cu, Ni and Zn on asexual reproduction and early development of the tropical sea anemone Aiptasia pulchella

Abstract: Currently few studies present sub-lethal toxicity data for tropical marine species, and there are no routine toxicity tests using marine cnidarians. The symbiotic sea anemone Aiptasia pulchella has been identified as a useful species for ecotoxicological risk assessment, and would provide a tropical marine cnidarian representative. Chronic sub-lethal toxicity tests assessing the effects of 28-day trace metal exposure on asexual reproduction in A. pulchella were investigated, and concentration-dependant reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Oocyte quality is a very important factor in reproductive success of a species, its impairment influencing reproductive functions and affecting the offspring quality. Recent studies have shown that Ni exposures affects fertilization success and early-life stages in a range of marine invertebrates like corals (Reichelt-Brushett, 1998; Howe et al, 2014 a ; Reichelt-Brushett & Hudspith, 2016), anemone (Howe et al, 2014 a , 2014 b ), sea urchin (Novelli et al, 2003; Phillips et al, 2003), abalone (Hunt et al, 2002), polychaete (Gopalakrishnan et al, 2007; Gopalakrishnan et al, 2008), and copepod (Mohammed et al, 2010), Daphnia (Taylor et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Oocyte quality is a very important factor in reproductive success of a species, its impairment influencing reproductive functions and affecting the offspring quality. Recent studies have shown that Ni exposures affects fertilization success and early-life stages in a range of marine invertebrates like corals (Reichelt-Brushett, 1998; Howe et al, 2014 a ; Reichelt-Brushett & Hudspith, 2016), anemone (Howe et al, 2014 a , 2014 b ), sea urchin (Novelli et al, 2003; Phillips et al, 2003), abalone (Hunt et al, 2002), polychaete (Gopalakrishnan et al, 2007; Gopalakrishnan et al, 2008), and copepod (Mohammed et al, 2010), Daphnia (Taylor et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…They exposed the pedal lacerates to Cd, Co, Cu, and Zn and observed effects on development to the juvenile stage (EC50s were 55 µg/L, 262 µg L, 5 µg /L, and 269 µg /L for Cd, Co, Cu, and Zn, respectively). Howe et al (2014b) used 28-d sublethal tests that observed asexual reproduction of symbiotic sea anemones (Aiptasia pulchella) to assess the toxicity of metals. They found 50% reductions in asexually reproduced juveniles (EC50) at 14 µg/L for Cu, 63 µg/L for Zn, and 107 µg/L for Ni.…”
Section: Chemical Toxicity and Testingmentioning
confidence: 99%
“…It is also referred to as being invasive and observed to have a pestand weedy-like nature in numerous studies (Steen, 1986;Grizel and Héral, 1991;Chen et al, 2008;Colin, 2009;Howe et al, 2012). A. pulchella is found throughout the tropical and subtropical oceans of the Indo-Pacific (Howe et al, 2014) with a documented distribution that spans French Polynesia, Japan, Hawaii, the central American coast of the eastern Pacific (Colin and Arneson, 1995;Howe et al, 2012), the Bay of Biscay (Gruet et al, 1976), and the Mediterranean Sea (Miralles et al, 2018a). There is no literature that describes the native environmental conditions (i.e.…”
Section: First Official Record Of An Invasive Live Rock Associated Sp...mentioning
confidence: 99%
“…Aiptasia sp. are not new to hitch-hiking, with studies reporting their introduction on oysters for aquaculture purposes (Grizel and Héral, 1991), by hull fouling (Farrapeiran et al, 2007;Canning-Clode et al, 2013) and on macroalgae, live rock, and corals purchased for marine hobbyists' aquaria (Calfo, 2004;Rhyne et al, 2004;Odom, 2012;Ram, 2013;Howe et al, 2014). Their rapid and weedy proliferation is a consequence of their ability to self-fertilize, which is a characteristic observed in founder organisms that have been introduced and establish themselves in new areas (Schlesinger et al, 2010).…”
Section: First Official Record Of An Invasive Live Rock Associated Sp...mentioning
confidence: 99%